EFEKTIVITAS GEL EKSTRAK PUTIH TELUR AYAM KAMPUNG TERHADAP PENYEMBUHAN LUKA PASCA PENCABUTAN GIGI TIKUS WISTAR JANTAN MELALUI PENGAMATAN JUMLAH SEL MAKROFAG - Hutagalung, Mangatas HP; Tarigan, Susiani (Jurnal Mutiara Kesehatan Masyarakat, 2018)
Tooth extraction causes injury to soft tissue and hard tissue in the former extraction area. Egg white can traditionally be used for the treatment of wounds. To determine the effectiveness of egg white extract gel for wound healing after tooth extraction of white mice by observing the number of macrophage cells.This study used an experimental method. The research subjects were 32 rats of male rats (Rattus novergicus) aged 2-3 months, divided into two groups, namely the Aquadest control group and the egg white gel treatment group. Extraction is carried out in the maxillary left incisors. Then rats were sacrificed on days 1, 3, 5 and 7. Observation of macrophage cells under a microscope with 40x magnification. The average number of macrophages in the treatment group was less than the Aquades control group and significantly decreased in the observation period (p <0.05). The administration of egg white extract gel in post tooth extraction socket wounds was effective in increasing the number of macrophage cells in the post-extraction wound healing process